Penerapan Kurikulum Merdeka dan Pembelajaran Mendalam pada Sekolah Indonesia Kuala Lumpur; SLR - Siti yulaikhah; Hari Muharam; Rita Retnowati; Nandang Hidayat; Suhendra (Journal of Innovative Islamic Education Management, 2026)
This systematic literature review (SLR) examines the implementation of the Merdeka Curriculum and pedagogical deep learning in Indonesian international school contexts, with a specific focus on Sekolah Indonesia Kuala Lumpur (SIKL). Guided by the PRISMA 2020 framework, this review synthesizes evidence from 20 peer-reviewed journal articles indexed in Scopus (Q1–Q4) and SINTA (1–6), published between 2020 and 2025. The review explores curriculum adaptation, instructional practices, teacher readiness, and learner outcomes conceptualized as Dimensi Profil Lulusan. The findings indicate that the Merdeka Curriculum aligns with global trends toward competency-based and learner-centered education, while pedagogical deep learning supports conceptual understanding, critical thinking, and transferable skills. Nevertheless, implementation in international school settings presents challenges related to curriculum coherence, professional development, and assessment alignment. This study contributes to international curriculum discourse by positioning Indonesian curriculum reform within the context of international schooling and deep learning pedagogy.